Biotechnological approaches in the production of plant secondary metabolites for treating human viral diseases: prospects and challenges - Mahmoudieh, Mohtaram; Naghavi, Mohammad Reza; Sobri, Zulfazli M.; Mohamad Azzeme, Azzreena; Abd-Aziz, Nazrin; Nik Abd Rahman, Nik Mohd Afizan; Alitheen, Noorjahan Banu; Hussin, Yazmin; Bahmanrokh, Ghazaleh; Akmal Baharum, Nadiya (Elsevier, 2024)
Over the last couple of decades, three highly pathogenic and deadly human coronaviruses have posed dreadful impacts on human life, namely SARS-CoV, MERS-CoV and SARS-CoV-2. In addition, many other viral diseases also affect various aspects of human well-being such as lifestyles and socio-economic conditions. Therefore, research on developing antiviral drugs should be progressively carried out to rapidly prevent or reduce the severity of infection for the current and future emerging infection with pandemic potential. Conventional antiviral drugs have been associated with high cost, toxicity and resistance issues. The use of medicinal plants and their secondary metabolites (SMs) with potential anti-inflammatory properties garners attention as a safer alternative for treating viral diseases. This review discussed various plant SMs with therapeutic potential for treating viral diseases. Due to various factors including low concentrations of the phytocompounds produced, relying on natural systems for producing medically important SMs is not sustainable. Thus, several biotechnology strategies such as metabolic engineering and genetic modification, in vitro production as well as gene editing to enhance the phytochemical compounds are also highlighted. Future perspectives on the potential of plant-based antiviral drugs as well as other strategies to treat viral diseases in humans are also elaborated. Altogether, this review gives a comprehensive view of the pharmaceutical importance of plant SMs as an alternative approach against viral diseases.